Unions, Work-Related Training, and Wages: Evidence for British Men - Marco Francesconi; Alison L. Booth; Gylfi Zoega (Institute for the Study of Labor (IZA), 2003)
Using data from the British Household Panel Survey from 1991 to 1996, the authors investigate the impact of union coverage on work-related training and how the union-training link affects wages and wage growth for a sample of full-time men. Relative to uncovered workers, union-covered men are more likely to receive training and also receive more days of training. In addition, union-covered men experience greater returns to training, and coveredtrained workers face a higher wage growth. While some of these findings have been found in previous studies, others are new. The wage results, in particular, suggest a rethinking is warranted of the conventional view that union wage formation in Britain reduces the incentives to acquire work-related training.
Keywords: J24; J31; J41; 330; general training; human capital; union coverage; wages; Lohn; Weiterbildung; Gewerkschaftlicher Organisationsgrad; Schätzung; Großbritannien